THE ROLE OF THE MINANGKABAU TRADITIONAL COMMUNITY'S CULTURE OF CONSENSUS BUILDING AS A PILLAR OF DEMOCRACY IN SUPPORTING THE SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Muhammad Yarif Arifin; Salle S; Muhammad Rinaldy Bima; M. Azham Ilham; Ar Rayhan Wiqra Ramadhan (Institut Agama Islam Negeri Bone, 2026)
Indigenous culture plays a vital role in shaping normative frameworks that support modern governance. This study examines the Minangkabau indigenous community’s tradition of consensus-based deliberation (musyawarah) as a democratic pillar that contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 16.7 on inclusive and participatory decision-making. Using a normative legal research method with a qualitative approach, the study explores how Minangkabau customary law integrates communal values into decision-making processes that promote social justice and poverty alleviation. In Minangkabau society, deliberation is not merely procedural but reflects a collective ethic where truth is determined through group consensus rather than individual assertion. This principle fosters inclusive governance, equitable outcomes and social cohesion. The study further analyzes the alignment between this indigenous practice and the Islamic principle of syuraa (consultation), which serves as a moral foundation for participatory democracy in Islamic jurisprudence. The results show that deliberative consensus functions as an effective participatory democracy mechanism based on local wisdom in realizing social justice and poverty alleviation. These findings confirm the relevance of integrating customary values and the principle of syūrā in strengthening equitable social governance and supporting the sustainable achievement of the SDGs.